7 GHz pulsed magnicon amplifier - Kozyrev, E.V.; Nikiforov, A.A.; Ostreiko, G.N.; Persov, B.Z.; Serdobintsev, G.V.; Shchelkunoff, S.V.; Tarnetsky, V.V.; Zapryagaev, I.A.; Nezhevenko, O.A.; Yakovlev, V.P. (Вопросы атомной науки и техники, 1999)
The work on creation of high-power microwave amplifiers with circular deflection of an electron beam has been carried out at INP since 1967.
In the latest set of experiments on 7 GHz magnicon almost all design parameters have been achieved: the output power of 55 MW, efficiency of 56 %, and gain of 72 dB. Experimental data are in an excellent agreement with simulation results obtained by the special magnicon computer codes. Achieved results allow us to consider a magnicon as an alternative power source for linear colliders applications.